2023
DOI: 10.3390/agronomy13051234
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Municipal Solid Waste Compost on the Tranformations of Phosphorus Forms in Soil

Abstract: Searching for a renewable phosphorus (P) source for agricultural soils has become a challenge of particular importance on a global scale. Depletion of the world’s phosphate resources as well as the risk of environmental problems caused by excessive P mobility have placed this topic among the most important environmental issues. The aim of this study was to analyse the transformation of phosphorus forms in municipal solid waste compost (MSWC) at different maturity stages, to assess the effects of their applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…It was found that the application of MSW to the soil increased the available phosphorus content and potentially mobile forms of phosphorus. However, it is noted that the use of MSW as a phosphorus source does not represent a serious environmental risk and could be a viable option, provided that the material is mature [14]. It is recommended to assess phosphorus availability and potential environmental risks when using compost as a phosphorus source rather than relying solely on total phosphorus content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was found that the application of MSW to the soil increased the available phosphorus content and potentially mobile forms of phosphorus. However, it is noted that the use of MSW as a phosphorus source does not represent a serious environmental risk and could be a viable option, provided that the material is mature [14]. It is recommended to assess phosphorus availability and potential environmental risks when using compost as a phosphorus source rather than relying solely on total phosphorus content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Horizon Depth (cm) TN (g/100 cm 3 ) TP (g/100 cm 3 ) TK (g/100 cm 3 ) MC (g/100 cm In the primary ecosystem, the form and circulation of phosphorus in soils are affected by factors such as the parent material, climate, environment, time, and topography. During the transition from native ecosystems to systems disturbed by human factors, the form, content, and distribution of soil phosphorus were affected by the input-output of soil and by human activities [29]. There is no gaseous form of phosphorus in the soil.…”
Section: Profilementioning
confidence: 99%